1002Job insecurity and health-related quality of life - a cross-sectional study in Sweden. (2nd September 2021) - Norström, Fredrik
Abstract: Background: Research shows that concern about job loss impacts negatively on health. However, no studies have examined how job loss affects health-related quality of life. The aim of this study is to examine how job insecurity affects health-related quality of life among Swedish employees. Methods: The sample comprised 967 participants (39%) out of 2, 500 randomly selected individuals. They answered a questionnaire that included a question about the risk of involuntary unemployment during the following three years and the EuroQol 5 dimensions (EQ-5D) instrument. EQ-5D responses were translated to a quality-adjusted life year (QALY) score with anchor points 1 (perfect health) and 0 (death). Of employed respondents without recent unemployment, 83 considered themselves to have at least some risk of unemployment, while 602 felt at most a small risk of unemployment. Inverse probability-weighted propensity scores were used in the analyses to estimate a risk difference. Gender, age, education level, marital status, and previous health were included as covariates. Results: There was a statistically significant lower QALY score by 0.068 points for those with job insecurity compared with those without job insecurity. There were also statistically significantly more problems due to job insecurity for usual activities (9.5% more), pain/discomfort (13.3% more), anxiety/depression (16.6% more), and EQ-5D's Visual Analogue Scale (4.5 point lower score). Conclusions: There was a strong indication that job insecurity affects health-related quality of life. Further studies are needed to better understand how job insecurity affects health. Key messages: More stable job positions should be prioritized by policy makers.